(untitled) (The Review of Diabetic Studies, 2024)
Mental health among healthcare professionals is increasingly recognized as a core determinant of healthcare quality, particularly within multidisciplinary care teams. This systematic review aimed to synthesize evidence published between 2019 and 2023 on the relationship between healthcare workers’ mental health and the quality of multidisciplinary healthcare, with a focus on nursing, family medicine, dentistry, medical laboratory services, and psychology. Following PRISMA 2020 guidelines, a comprehensive search of PubMed/MEDLINE, Scopus, Web of Science, CINAHL, and PsycINFO identified 1,355 records, of which 50 studies met the inclusion criteria for qualitative synthesis. The findings consistently demonstrated that poor mental health—most notably burnout, chronic stress, anxiety, and psychological distress—was associated with reduced patient safety, lower perceived and measured quality of care, impaired teamwork and communication, and increased turnover intention across professional groups. Nursing and primary care settings provided the strongest evidence linking burnout to patient safety incidents and poorer patient experiences, while emerging evidence from dentistry, medical laboratories, and psychology highlighted risks to care reliability, diagnostic quality, and service continuity. Across studies, interprofessional collaboration and organizational climate were identified as key mechanisms mediating the relationship between mental health and care quality. Despite growing attention to this topic, the evidence remains fragmented by profession and outcome type, underscoring the need for integrated, multidisciplinary approaches to workforce mental health. Overall, this review supports the conclusion that promoting healthcare workers’ mental well-being is not only an occupational priority but also a fundamental strategy for improving the quality and safety of multidisciplinary healthcare systems.